Handbook of anatomical models for radiation dosimetry - Xie, George Xu (CRC Press, 2014)
Covering the history of human model development, this title presents the major anatomical and physical models that have been developed for human body radiation protection, diagnostic imaging, and nuclear medicine therapy. It explores how these models have evolved and the role that modern technologies have played in this development.